(3YedjGJ ZSjd GdCehGd Hjf GdGbJUGO GdGSdGej hGdGbJUGO GdhVYjs - (3YHO eMehO gdGd(B, (3GdSejQGJs ((3YeGf(B:s (3OGQ GdfaGFS(B,s, 2009)
(3eGgjI h CSHGH h fTCI YedjGJ ZSjd GdGehGd , GdeQGMd GdJj JeQ HgG YedjGJ ZSjd GdCehGd h GdYhGed GdJj SGYOJ Ydi GfJTGQgG , eUGOQ GdCehGd ZjQ GdeTQhYI GdNGVYI dYedjGJ ZSjd GdCehGd h ehba GdTQjYI GdGSdGejI efgG , GdBKGQ GdGbJUGOjI h GdGLJeGYjI dYedjGJ ZSjd GdCehGd h Gdehba GdbGfhfj h GdTQYj h GdYdGL dgPg GdYedjGJs
Keywords: (3GdGbJUGOs; (3GdGbJUGO GdGSdGejs; (3GdLQGFe GdJLGQjIs; (3LQGFe GdCehGds